The retirement expectations of middle-aged individuals - Deborah A. Cobb-Clark; Steven Stillman (Institute for the Study of Labor (IZA), 2006)
We use the first three waves of the Household Income and Labour Dynamics in Australia (HILDA) Survey to examine the retirement plans of middle-aged workers (aged 45-55). Our results indicate that approximately two-thirds of men and more than half of women appear to be making standard retirement plans. At the same time, more than one in five individuals seem to have delayed their retirement planning and approximately one in ten either do not know when they expect to retire or expect to never retire. Retirement plans are closely related to current labor market position. Specifically, forming expectations about the age at which one will leave the labor market appears to be easier for workers in jobs with well-defined pension benefits and standard retirement ages. Moreover, those who report that they do not know when they expect to retire do in fact appear to face greater uncertainty in their retirement planning. Those who anticipate working forever seem to do so out of concerns about the adequacy of their retirement incomes rather than out of increased job satisfaction or a heightened desire to remain employed. Finally, men alter their retirement plans in response to labor market shocks, while women are more sensitive to their own and their partners' health changes.
urn:nbn:de:101:1-20080702311
Keywords: 330